Analisis Pengaruh Rasio Likuiditas Dan Rasio Solvabilitas Terhadap Profitabilitas Pada Perusahaan PT Bukalapak Tbk Periode 2023-2024 - Elsa, Elsa Elfitri Alzahra; Deri Apriadi (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the influence of liquidity and solvency ratios on the profitability of PT Bukalapak Tbk during the 2023–2024 period. The variables used are Current Ratio (CR) for liquidity, Debt to Asset Ratio (DAR) for solvency, and Return on Equity (ROE) for profitability. The research applies a descriptive quantitative method with secondary data obtained from the company's official financial reports. Data were analyzed using multiple linear regression with SPSS version 26. The results show that the Current Ratio has a significant positive effect on Return on Equity, while the Debt to Asset Ratio has no significant partial effect. However, both variables together significantly influence profitability. The coefficient of determination indicates that CR and DAR explain 99.5% of the variation in ROE, suggesting that liquidity is a dominant factor in determining profitability at PT Bukalapak Tbk. These findings provide insights for financial management strategies in tech-based companies.